The COVID-19 pandemic and global health from the perspective of critical bioethics - Izaguirre, Manuel (2021)
Globalization and global health are consequences of the decisions of government officials who generated public policies, modes of production and development, without thinking about the benefit of people and the environment, acting without ethical or social responsibility when not focusing on the person human right that prioritizes health and equity for all people, valuing equality in the field of global politics, economic and technological globalization and in global problems related to the environment, global warming and flows migratory, whose understanding requires knowing the relationships between human health, environment and wealth, prioritizing the optimal survival of humanity, the final goal of global bioethics, to guarantee human dignity and universal human rights, including the right to health, all time, that “universal morality is a historical product of human experience”, being practical and practical lessons rendered over time. Therefore, ethical decisions to solve moral conflicts during the pandemic must be rational and not just emotional, circumscribed in the sphere of social and distributive justice in order to save the greatest number of lives based on the principles of ethics, social, contrasting the ethical principles of the individual sphere such as autonomy that is privileged when it does not harm others and justice that limits it when freedom is deprived for isolation purposes.